Transient hypertrophic cardiomyopathy and hypertension associated with hydrocortisone in preterm infant: A case report. Issue 33 (August 2019) - Jiang, Jingbo; Zhang, Jiawen; Kang, Mengmeng; Yang, Jie
Abstract: Rationale: Hypertrophic cardiomyopathy (HCM) is a heterogeneous, usually familial disorder of heart muscle. The hypertrophic form of cardiomyopathy is frequently genetic, or as part of several neuromuscular disorders. In neonates, especially prematurity, HCM could also be secondary to corticosteroid treatment. Patient concerns: We reported here a 34 weeks gestational age preterm infant presented with profound cardiomegaly after multiple doses of hydrocortisone used to treat blood pressure instability associated with septic shock and persistent pulmonary hypertension (PPHN). Diagnosis: Patient presented auscultation of a grade III/IV harsh systolic ejection murmur from day 14, which was absent before. Profound cardiomegaly was indicated at chest film at day 30. Echocardiography showed severe thickening of the IVS (13.8 mm, z score = 8.29) and mild thickening of the posterior left ventricular wall (LVPW, 6 mm). Interventions: Propranolol and captopril were started along with supportive care. The patient was also admitted to NICU for further treatment with 24-hour Holter electrocardiographic monitoring. Outcomes: A reversible course was observed without left ventricular outflow tract obstruction nor arrhythmias within 4 weeks. Lessons: The risk/benefit ratio must be carefully considered when corticosteroids are used in prematurity. Monitors such as echocardiography and electrocardiograph should be conducted in order to guide cardiovascular management. Systematic surveys of the incidence of cardiac complications in a larger population of preterm infant treated with corticosteroid are needed in the future.